A Possible Mechanism: Genistein Improves Metabolism and Induces White Fat Browning Through Modulating Hypothalamic Expression of Ucn3, Depp, and Stc1 - Zhou, Liyuan; Xiao, Xinhua; Zhang, Qian; Zheng, Jia; Li, Ming; Deng, Mingqun (Frontiers in Endocrinology, 2019)
Bioactive food components have gained growing attention in recent years. Multiple studies demonstrated that genistein had beneficial effects on metabolism. However, the exact mechanism by which genistein improves metabolism remains unclear, especially the central regulation. This study was designed to evaluate whether addition of genistein to the high-fat diet could counter metabolic disorders and whether these alterations were associated with gene expression in hypothalamus. C57BL/6 mice were fed either a high-fat diet (HF), high-fat diet with genistein (0.25 g/kg diet) (HFG) or a normal control diet (CON) for eight weeks. Body weight was assessed during the study. After eight-week intervention, content of inguinal subcutaneous adipose tissue (SAT), perirenal visceral adipose tissue (VAT) and brown adipose tissue (BAT) were weighed. Glucose tolerance test, the serum levels of insulin and lipid were assessed. The mRNA of browning marker was detected in the white fat. The hypothalamus was collected for whole transcriptome sequencing and reverse transcription quantitative PCR validation. The results demonstrated that mice fed HFG diet had lower body weight and SAT mass, decrease levels of low-density lipoprotein cholesterol and free fatty acids, higher browning marker of Ucp1 and Cidea in WAT and an improvement in glucose tolerance and insulin sensitivity compared with those in HF group. Transcriptome sequencing showed that there were three differentially expressed genes in hypothalamus among the three groups, including Ucn3, Depp and Stc1, which were significantly correlated with the browning markers in WAT and insulin sensitivity. Thus, regulating gene expressions in hypothalamus is a potential mechanism for genistein improving metabolism and inducing WAT browning, which may provide a novel target for the precaution and treatment of T2DM.